Case of intracranial vertebral artery dissection in young age - (:unkn) unknown (ELSEVIER SCIENCE INC, 1997)
Stroke in childhood is rare and has its own characteristic findings, Vertebrobasilar ischemia due to trauma in this age group has been described, but its specific features have not yet been clearly defined. Dissection of vertebral artery is one of the causes of vertebrobasilar ischemia that is very uncommonly detected in the intracranial portion of the posterior circulation in childhood. We report a 14-year-old boy with a history of neck trauma and transient vertigo attacks who presented with brainstem and cerebellar ischemic findings. Due to the large left cerebellar infarct size compressing the fourth ventricle, we performed emergent posterior fossa decompression, Digital cerebral subtraction angiography revealed left vertebral artery dissection beginning at the V1 portion to the level of V4 and distal thrombosis of basilar artery, After 2 months, he was discharged from the hospital with minor neurologic deficit with anticoagulation therapy, Due to better outcome in childhood, early investigation for intracranial dissection should be included in the evaluation of posterior circulation infarcts in this age group. (C) 1997 by Elsevier Science Inc.